Exploração do conceito de multiplicação de matrizes através de tecnologias digitais: sites e softwares educativos - Chereguini, Ana Ligia Costa (2013)
The present study lies in the learning context where there is an alleged disinterest and difficulties of students when presenting the contents of arrays. From the contents above, the study aimed to describe the instructional sequence that aimed to provide an understanding of the Matrices content by students of 2nd year of secondary education, focusing on the use of technology as an ally in solving problems. In the first and second stage of the development of this instructional sequence it was detected through examples and exercises, that some students presented themselves unmotivated in face of difficulties regarding the resolution of problems involving content prerequisites matrices, such as handling of negative numbers in mathematical operations. From this preliminary assessment, attention was given to resume the content identified as deficient and concomitant and emphatically it was made use and application of educational software for teaching arrays. At the end of the five moments involving this instructional sequence, which occurred over twelve lessons, it was possible to arouse the curiosity of students and propitiate them to understand the content of matrices and hence promote greater involvement with the subject of Mathematics. Throughout the study presents considerations on the various difficulties encountered during the development of this work in order to teach the concept of matrix multiplication.